Coverage and contextual factors associated with insecticide-treated net use among women of reproductive age in Nigeria: evidence from the 2021 malaria indicator survey data. - Amadou Barrow; Oluwakemi Christie Ogidan; Chimezie Igwegbe Nzoputam; Michael Ekholuenetale (PLOS Global Public Health)
Nigeria continues to face a serious public health problem due to malaria, which contributes around 27% of all cases worldwide. Although insecticide-treated nets (ITNs) are essential interventions for preventing malaria, their use in Nigeria is still sub-optimal. Understanding the factors influencing ITN use is essential to improve malaria control strategies. This study aimed to investigate the prevalence of and factors associated with ITN use among women of reproductive age in Nigeria. We conducted a secondary data analysis of the 2021 Malaria Indicator Survey (NMIS). The sample included 14,476 women of reproductive age (15-49 years) from 567 clusters across Nigeria's six geopolitical zones. Multilevel logistic regression was used to examine the contextual factors associated with ITN use, accounting for both fixed and random effects. Statistical significance was set at p<0.05, with 95% confidence intervals reported for all estimates. The weighted prevalence of ITN use was 41.5% (95% CI: 39.7, 43.3). The results showed Muslim women had 21% (aOR= 0.79; 95% CI: 0.67-0.94) lower odds of ITN use, when compared with the Christian women. Those who had living children were more likely to report ITN use, when compared with women with no child. The non-poor women had higher odds of ITN use, when compared with the poor women (aOR= 1.35; 95% CI: 1.19-1.52). In addition, women from multi-ethnic had 26% lower odds of ITN use, when compared with those from mono-ethnic community (aOR= 0.74; 95% CI: 0.57-0.94). The geographical region was significantly associated with ITN use among Nigerian women. Those from high-level community poverty had 53% reduction in the odds of ITN use, when compared with women from low-level community poverty (aOR= 0.47; 95% CI: 0.32-0.68). ITN use among women of reproductive age in Nigeria remained below the national target. Interventions to increase ITN use should consider the complex interplay of individual and community-level factors. Targeted strategies addressing socioeconomic disparities, leveraging cultural contexts, and implementing community-based approaches are crucial for improving ITN utilization and reducing the malarial burden in Nigeria.